Revisiting Resource-Based View in the Digital Age: From Tangible Assets to Data Capital - Harper, Emily Harper; Thompson, Liam Thompson (ICON Publisher, 2025)
This conceptual paper revisits the Resource-Based View (RBV) in the context of the digital economy, arguing that data capital has become the primary foundation of competitive advantage. Traditional RBV assumptions about tangible and static resources no longer capture the dynamic nature of digital competition. Through theoretical synthesis and literature integration, the study explores how data-driven capabilities transform the processes of resource accumulation, orchestration, and renewal. The findings highlight that data capital — characterised by scalability, renewability, and relational embeddedness — demands a redefinition of the VRIN framework. Firms gain sustainable advantage not merely by owning data but by transforming it into knowledge through analytics, dynamic capabilities, and digital literacy. The study proposes a new conceptual model, the Data-Based View (DBV), integrating insights from dynamic capabilities theory and ecosystem logic. It contributes to theory by extending RBV into the digital context and offers managerial implications for building data-centric strategies, governance, and human–technology complementarities. While conceptual in nature, this study provides a foundation for future empirical research to measure data capital and test its impact on firm performance. Ultimately, it asserts that the strategic essence of the digital age lies not in asset ownership, but in data orchestration and capability amplification.